Graphene milling dynamics during helium ion beam irradiation. (November 2018) - Kim, Songkil; Dyck, Ondrej; Ievlev, Anton V.; Vlassiouk, Ivan V.; Kalinin, Sergei V.; Belianinov, Alex; Jesse, Stephen; Ovchinnikova, Olga S.
Abstract: We explore the potential of the Helium Ion Microscope (HIM) as a tool for direct-write patterning of graphene and describe the underlying processes of graphene milling with image data processing. Controlled helium ion irradiation of suspended graphene conducted while monitoring the mill in-situ revealed the localized formation of nanopores, their growth, and coalescence. We also explore the effects of defects on the milling dynamics, and show that pre-exposed membranes rupture by cracking and rapid crack propagation at the edges of the growing defects. The mechanism for the rupturing process is described by local defect formation by excessive irradiation of helium ions, dictated by the scanning direction of the beam. These findings enrich fundamental understanding of the graphene milling process with a helium ion beam that, is necessary for high-resolution and high throughput patterning of graphene with nanoscale precision. Graphical abstract: Image 1